PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN KINERJA LINGKUNGAN TERHADAP KINERJA PERUSAHAAN - Ayu Yulia Sari; Mukhlizul Hamdi; Kasman Karimi (Jurnal Kajian Akuntansi dan Auditing, 2022)
This study uses the variable mechanism of good corporate governance (Independent Commissioner, Board of Directors and Audit Committee) and environmental performance on company performance. Sample 16 Companies The consumer goods industry sector registered on the 2016-2020 IDX using the purposive sampling method and using secondary data. To prove the hypothesis used in this study, quantitative analysis methods are used. Data testing is carried out using SPSS 16.0. In this method the data processing stage is carried out with the stages of statistical testing. The results of hypothesis testing, only independent commissioners have a significant effect on company performance while the board of directors, audit committees and environmental performance have no effect on company performance.